2001
DOI: 10.4269/ajtmh.2001.64.97
|View full text |Cite
|
Sign up to set email alerts
|

The neglected burden of Plasmodium vivax malaria

Abstract: Abstract. We estimate that the global burden of malaria due to Plasmodium vivax is ϳ70-80 million cases annually. Probably ϳ10-20% of the world's cases of P. vivax infection occur in Africa, south of the Sahara. In eastern and southern Africa, P. vivax represents around 10% of malaria cases but Ͻ 1% of cases in western and central Africa. Outside of African, P. vivax accounts for Ͼ 50% of all malaria cases. About 80-90% of P. vivax outside of Africa occurs in the Middle East, Asia, and the Western Pacific, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
662
1
19

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 852 publications
(685 citation statements)
references
References 48 publications
3
662
1
19
Order By: Relevance
“…Transmission intensity in Vietnam is sufficiently low to warrant consideration of eradication therapy for infected individuals, as the likelihood of relapse is expected to be much greater than that of reinfection. Eradication requires a protracted course of primaquine (Mendis et al, 2001), and the significant prevalence of G-6-PD deficiency documented here is of considerable clinical importance. Further population studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission intensity in Vietnam is sufficiently low to warrant consideration of eradication therapy for infected individuals, as the likelihood of relapse is expected to be much greater than that of reinfection. Eradication requires a protracted course of primaquine (Mendis et al, 2001), and the significant prevalence of G-6-PD deficiency documented here is of considerable clinical importance. Further population studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of this parasite to chloroquine is geographically still limited, 96 though likely to increase. Although it causes recurring and debilitating infections, P vivax rarely kills.…”
Section: Plasmodium Vivax Malariamentioning
confidence: 99%
“…16 They attributed these elevated serum bilirubin levels to intravascular haemolysis and associated renal failure, leading to decreased excretion of bilirubin. [17][18][19] Murthy et al in their study of 95 patients observed that high serum bilirubin levels in malaria were associated with a more severe course of illness, and with higher incidence of complications and poor prognosis because of histopathological changes to the liver. 11…”
Section: Discussionmentioning
confidence: 99%